Masks, Marriage and the Byzantine Mandylion: Classical Inversions in the Tenth Century. Narratio de translatione Constantinopolim imaginis Edessenae - Peers, Glenn (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2006)
This article examines the theatrical and matrimonial allusions in the tenthcentury hagiography of the Byzantine touch-relic of Christ: the Mandylion. The legend of the Mandylion was said to have been created when Christ washed his face and left a likeness of his face on the cloth with which he dried himself. It became immensely popular in the Byzantine and East Christian worlds, and it stood for God's protection of his new chosen people, for his imminence in the material world, and for a divine ratification of Christian figural art. This article argues that the Mandylion's arrival at Edessa and its reception in the king's chamber invests the face of Christ with powerful possibilities of real union with God. Those possibilities were expressed in terms educated Byzantines could have recognized, visceral inversions of the classical past and of the Christian present. Not only were the possibilities recognizable, but they also underscored the legitimacy of sole rule by Constantine VII through parallels to the first Christian king, Abgar of Edessa.